2023
DOI: 10.17507/tpls.1304.27
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Second Language Request Strategies by a Chinese Undergraduate Student Majoring in Business English

Abstract: Making requests is one of the most commonplace pragmatic behaviors in daily interactions. This present paper attempts to specifically examine the use of second language (L2) request strategies by a single English major in China. By providing four different role-play scenarios in which relative power (+/–P) and social distance (+/–D) were deliberately designed as the contextual constraints, while low ranking of imposition (–R) was kept constant, this case study elicited and audio-recorded the participant’s conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A more recent study by Zhang et al [9] examined the relationship between academic discourse strategy ability and career success among postgraduate students majoring in STEM fields. The study involved a sample of 800 postgraduate students and utilized a mixed-methods approach to collect data [10][11][12][13]. The results showed that students with higher levels of academic discourse strategy ability reported greater success in their career pursuits, indicating the importance of this skill for professional advancement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A more recent study by Zhang et al [9] examined the relationship between academic discourse strategy ability and career success among postgraduate students majoring in STEM fields. The study involved a sample of 800 postgraduate students and utilized a mixed-methods approach to collect data [10][11][12][13]. The results showed that students with higher levels of academic discourse strategy ability reported greater success in their career pursuits, indicating the importance of this skill for professional advancement.…”
Section: Literature Reviewmentioning
confidence: 99%